Detection And Prevalence Of Gastrointestinal Helminthes In Samosir Goats On Samosir Island, North Sumatra, Indonesia - Mudhita Zikkrullah Ritonga; Andhika Putra; Sukma Aditya Sitepu; Suriadi Suriadi; Zidan Aman Bakti; Ari Kurniawan; Tri Surya Putra; Rony Suranta Pinem (The International Journal of Tropical Veterinary and Biomedical Research, 2020)
Abstract